PRAKTIK PENGGUNAAN MEMBER CARD DALAM TRANSAKSI JUAL BELI DITINJAU DARI PERSPEKTIF HUKUM POSITIF DAN HUKUM ISLAM : Studi Kasus di Griya Mart Haurgeulis, Indramayu - Azmi Faizah Nahri; Irvan Iswandi (Melati Institute, 2022)
Member Card or in Arabic Bithaqatu at Takhfidh is a card where the owner will get a discount from the price of goods or some services provided by certain companies. There is a problem in the practice of using Member Cards in buying and selling transactions at Griya Mart Haurgeulis, Indramayu. In practice, the card must be charged an administration fee of Rp 20,000 and the active period or card renewal period is to be applied for one year by issuing the same additional costs. This thesis is the result of research using library research methods or library research and field research methods. Data analysis method used in this research is descriptive research. Data collection is obtained through observation, namely conducting direct observations in the field to get a real picture of the activities being examined. The data sources used are primary and secondary data from the library, as well as data from research objects (individuals or institutions, communities and others) based on facts that are happening at this time. In this study it can be seen that there are several problems, including the problem of extending the active period of Member Cards with an additional fee of Rp 20,000. Usually membership fees are only paid at the beginning of registration and the customer immediately gets the membership card, where things like this are feared to contain the element of gharar inside it. The results showed that the practice of using member cards in buying and selling transactions at Griya Mart was in accordance with positive law where the giving of discounts was true and no party felt disadvantaged. According to Islamic law the practice of using member cards in buying and selling transactions at Griya Mart has fulfilled the terms and conditions of sale and purchase and is in accordance with the principles of muamalah.